+0  
 
0
235
1
avatar

1:

 

2: 

 Dec 15, 2017
 #1
avatar+94619 
+1

1.

 

2x^2  -  4x   +   16  = 0      divide through by 2

 

x^2  -  2x  +   8   =  0      complete the square on  x

 

x^2 -  2x   +  1    =  - 8  +  1

 

(x - 1)^2  =   - 7

 

x  - 1   =   ±√-7

 

x  =   ± i√7    +  1

 

The second answer is correct

 

2. 

 

Here are the answers that go into each box 

 

x^4  +  2x^2y^2  + y^4

 

x^4  +  4x^2y^2

 

x^2 (x^2 + 4y^2)

 

 

cool cool cool

 Dec 15, 2017

18 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.